You nest here with me - Yolen, Jane; Stemple, Heidi E. Y.; Sweet, Melissa, 1956- (Honesdale, Pennsylvania : Boyds Mills Press, an imprint of Highlights, 2015)
A mother tells her child at bedtime how and where different birds make their nest, just like the child nests in a home with her mother.
Keywords: Birds -- Nests -- Fiction; Bedtime -- Fiction; Mother and child -- Fiction; Stories in rhyme; Birds -- Nests -- Fiction; Bedtime -- Fiction; Mother-child relationship -- Fiction; Stories in rhyme